Snail Shell (Rostellariella) as a Low Cost Adsorbent for Safranine Dye Removal from Aqueous Solution (Baghdad Science Journal, 2024)
In this paper, snail shell powder was used an adsorbent for safranine dye due to its low cost, high efficiency and high adsorption capacity. Experiments were conducted at a temperature of 298 K to find out the effect of pH, concentration, weight, ionic strength and equilibrium time. Also, the best conditions for the adsorption of Safranin dye were implemented at a weight of 0.0200 g of snail shell powder. The removal ratio was 96.09 % at a concentration of 9mg/L and 20 minutes as adsorption time at a temperature of 298 K. The objective of the study to analyze the equilibrium isotherms. The data collected from the experiments were analyzed by the three models of adsorption: Langmuir, Temkin, and Freundlich. The data were suitable for Freundlich isotherm. The calculated thermodynamic information of the process shows that the removal process occurs through an active exchange of random molecules.